Loss of Gadkin Affects Dendritic Cell Migration In Vitro. - Hannah Schachtner; Mirjana Weimershaus; Vanessa Stache; Natalia Plewa; Daniel F Legler; Uta E Höpken; Tanja Maritzen (PLoS ONE)
Migration is crucial for the function of dendritic cells (DCs), which act as outposts of the immune system. Upon detection of pathogens, skin- and mucosa-resident DCs migrate to secondary lymphoid organs where they activate T cells. DC motility relies critically on the actin cytoskeleton, which is regulated by the actin-related protein 2/3 (ARP2/3) complex, a nucleator of branched actin networks. Consequently, loss of ARP2/3 stimulators and upstream Rho family GTPases dramatically impairs DC migration. However, nothing is known yet about the relevance of ARP2/3 inhibitors for DC migration. We previously demonstrated that the AP-1-associated adaptor protein Gadkin inhibits ARP2/3 by sequestering it on intracellular vesicles. Consistent with a role of Gadkin in DC physiology, we here report Gadkin expression in bone marrow-derived DCs and show that its protein level and posttranslational modification are regulated upon LPS-induced DC maturation. DCs derived from Gadkin-deficient mice were normal with regards to differentiation and maturation, but displayed increased actin polymerization. While the actin-dependent processes of macropinocytosis and cell spreading were not affected, loss of Gadkin significantly impaired DC migration in vitro, however, in vivo DC migration was unperturbed suggesting the presence of compensatory mechanisms.